Flash Pyrolysis Kinetics of Extracted Lignocellulosic Biomass Components - Pielsticker, Stefan; Gövert, Benjamin; Umeki, Kentaro; Kneer, Reinhold (Frontiers in Energy Research, 2021)
Biomass is a complex material mainly composed of the three lignocellulosic components: cellulose, hemicellulose and lignin. The different molecular structures of the individual components result in various decomposition mechanisms during the pyrolysis process. To understand the underlying reactions in more detail, the individual components can be extracted from the biomass and can then be investigated separately. In this work, the pyrolysis kinetics of extracted and purified cellulose, hemicellulose and lignin are examined experimentally in a small-scale fluidized bed reactor (FBR) under N2 pyrolysis conditions. The FBR provides high particle heating rates (approx. 104 K/s) at medium temperatures (573–973 K) with unlimited reaction time and thus complements typically used thermogravimetric analyzers (TGA, low heating rate) and drop tube reactors (high temperature and heating rate). Based on the time-dependent gas concentrations of 22 species, the release rates of these species as well as the overall rate of volatiles released are calculated. A single first-order (SFOR) reaction model and a 2-step model combined with Arrhenius kinetics are calibrated for all three components individually. Considering FBR and additional TGA experiments, different reaction regimes with different activation energies could be identified. By using dimensionless pyrolysis numbers, limits due to reaction kinetics and heat transfer could be determined. The evaluation of the overall model performance revealed model predictions within the ±2σ standard deviation band for cellulose and hemicellulose. For lignin, only the 2-step model gave satisfying results. Modifications to the SFOR model (yield restriction to primary pyrolysis peak or the assumption of distributed reactivity) were found to be promising approaches for the description of flash pyrolysis behavior, which will be further investigated in the future.